(untitled) (Development Service Industry Management, 2025)
The article examines how Ukrainian retail network structures adapt to the combined challenges of war, European integration, energy disruptions, and digital transformation, when it is necessary to move from situational solutions to systemic approaches at the business model, logistics, and compliance levels. The goal is to form a holistic vision of the adaptation of Ukrainian retail network structures: to clarify the factors and models of adaptation, compare them in different sectors, and present a generalized matrix of tools with critical comments and current cases. A combination of theoretical and empirical approaches is used: critical review and systematization of scientific sources; statistical analysis of secondary market data (dynamics of openings/closings), case method, content analysis of network management decisions with subsequent grouping of tools by challenge blocks; analytical generalization of results with a focus on practical applicability. Time horizon — 2019–2025 with an emphasis on 2022–2025. The study clarifies external (regulatory, technological, military, energy) and internal (organizational, financial, personnel, digital) adaptation factors for the Ukrainian context. Sectoral differences in the choice of network models are shown: the dominance of corporate networks in food retail, the wider use of franchising in pharmacy, hybrid formats in online trading. The current market dynamics of 2024 are systematized (the structure of new discoveries and regional concentration). A matrix of adaptation tools “challenge - tools - examples of networks - critical commentary” has been developed, covering war, logistics, European integration, certification, blackouts, energy stability, digitalization, innovation, sustainable development, with the fixation of costs, limitations and side effects. The conclusion is made about the predominantly reactive nature of current measures and the vectors of the transition to systemic sustainability are outlined (logistics and energy planning, compliance with operations, balance of economic, social and environmental goals). The results obtained are useful for managers and functional directors of chain retailers (operations, logistics, IT/digitalization, compliance/ESG), industry analysts and consultants, as well as state and municipal authorities that form policies to support trade in conditions of increased risks.